A Study of Training Programmes: a case of MANAGE - Vikram Singh,; G.Jaya,; A.5. Charyulu, (Journal of Agricultural Extension Management, 2025)
This study was undertaken to have insight into the important variables that influence the effectiveness of training programmes and enable the trainer to reorient them, suitably dovetailing to the needs of the trainees and the organizations. The objectives are to assess the strengths and weaknesses in terms of design, delivery, content creation and training methodology and suggest ways and means to bring about overall improvement in training programmes. Results reveal that MANAGE training programmes were found to be designed appropriately, content matched participants' needs and helped to realize program objectives; training methodology was found suitable and the training contributed to performance back at work. Some of the recommendations include, giving adequate space to emphasize skill development and field application of the content covered; Training Need Assessment (TNA) as an important requirement; field visits; greater use of audio visual aids, panel discussions. Some follow up exercise with the trainees is also suggested to not only help trainees to monitor progress but also help MANAGE to improve the quality of future training programmes